PENGARUH DUKUNGAN KELUARGA TERHADAP TUMBUH KEMBANG BALITA - Nova Linda Rambe; Khairun Nisa (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Family members are the most important part in the process of developing toddlers in carrying out positive socialization in the surrounding environment. Basically, children have a need to achieve growth and development. This is a challenge for family members to be more alert and sensitive to the actions around them that can impact the child's development in the future. The focus of the problem in this study refers to the role of parents in supporting the growth and development of toddlers. Respondents in this study were 40 respondents who had toddlers at the Sidorejo Hilir Sub-Health Center. The sampling technique used is using the non-probability sampling method, because this study aims to find out in depth how the response of family support to toddlers. The purpose of this study was to find out how much influence family support had on the growth and development of toddlers at the Sidorejo Hilir Community Health Center. Research results, as many as 52.5% of respondents had toddlers aged 20-35 years, toddlers aged 2-3 years, toddler growth of 47.5% was categorized as thin, and 50% of toddlers' development was stated to be doubtful, 62.5% family support has made sufficient efforts for the growth and development of toddlers. In conclusion, the role of the family is very significantly related to the growth and development of toddlers. This can be seen from toddlers who are declared thin growth and are declared doubtful in their development because the role of support is in the sufficient category.